(untitled) (Jurnal Pembangunan Sosial, 2010)
The issue of work culture has become extremely crucial because of late there have been numerous complaints from the FELDA participants regarding the services of its officers. This research critically analyses the behavior determinant towards work culture for the FELDA officers. There are several main factors that influence their behavior namely the demographic location, recognition, work performance and responsibility. The demographic factors such as gender, age, marital status, academic qualification and work experience are used as moderator’s variables. The findings show that there is a positive correlation between these variables and the work culture.